2021
DOI: 10.1002/pamm.202000315
|View full text |Cite
|
Sign up to set email alerts
|

Partitioned simulation of the acoustic behavior of flexible marine propellers using finite and boundary elements

Abstract: In the last years, classification societies have announced several specifications regarding the , limitation of the noise level of ships. Accordingly, the prediction of the acoustic signature of cavitating propellers, which are the main source for noise generation, has attracted a lot of interest. For an accurate numerical simulation of the underlying physics, the deformation of the propeller has to be taken into account, which results in a fluid-structure interaction (FSI) problem. In order to utilize differe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…CFRP propellers have already been used for large commercial vessels -with promising results [1]. Previous works have demonstrated that flexible marine propellers, apart from reducing the weight, allow for a reduction of cavitation which leads to a decrease in noise emission [2] [3]. Taking advantage of the anisotropy of composite propellers, it is also possible to increase the efficiency [4].…”
Section: Introductionmentioning
confidence: 99%
“…CFRP propellers have already been used for large commercial vessels -with promising results [1]. Previous works have demonstrated that flexible marine propellers, apart from reducing the weight, allow for a reduction of cavitation which leads to a decrease in noise emission [2] [3]. Taking advantage of the anisotropy of composite propellers, it is also possible to increase the efficiency [4].…”
Section: Introductionmentioning
confidence: 99%